Conservation perceptions and attitudes regarding monitor lizards in West Bengal, India - Shreya Bhattacharya; Syeda Zuboor Zia; Santanu Mahato; Ravi Kumar Gangwar; Neha Singh; Mark Auliya; André Koch (Nature Conservation)
Local and illegal exploitation of wildlife is particularly widespread in highly populated and bio-diverse countries such as India. In such countries, illicit utilization practices and how these are perceived among local communities are commonly not well-documented. Due to a lack of data, and environmental education measures to protect ecosystems and biodiversity, the extent of this exploitation appears immense and often goes unnoticed. Therefore, in 2019, a series of awareness workshops targeting the conservation of wildlife focused on monitor lizards (Varanidae) was conducted in five districts of West Bengal, India. The environmental awareness workshops were conducted through PowerPoint slide presentations and questionnaires collecting baseline data from the participants regarding their perceptions and relationships to the three species of Varanus recorded for West Bengal. Our findings reveal specific human attitudes and varying local utilization patterns of monitor lizards. This study was the first to communicate and spread awareness in the study areas about why the conservation of local wildlife such as Varanus species is important for ecosystems and human well-being based on the ‘Nature Contributions to People Concept’.